Konsep Pendidikan Islam Berbasis Tauhid Pada Masa Rasulullah - Busra, Aminudin; Roza, Ellya (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The aim of this research is to analyze the concept of Islamic education based on monotheism during the time of the Prophet. This type of research is a library study. Data collection with documentation. Data analysis with SLR. The research results obtained are The concept of Islamic education based on monotheism during the time of the Prophet was the main foundation in the formation of Muslim individuals with character. Education at that time was not only focused on academic aspects, but also strengthened faith and awareness of the oneness of Allah. The Prophet as the main role model paid great attention to moral, spiritual and social education, which is based on monotheism. Through these teachings, Muslim society at that time was able to build a strong personality, uphold the values of truth, justice and compassion in all aspects of life, thereby creating a harmonious and dignified society.